Peran dan Fungsi Dewan Pengawas Syariah (Shari’a Supervisory Board) dalam Perbankan Syariah di Indonesia - Nikmah Rahmawati (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2014)
Shari’a Supervisory board (DPS) is basically the extension of National Shari’a Board (DSN) in realizing the religious advices instructed by National Shari’a Board (DSN). Shari’a Supervisory Board (DSN) plays as the supervisor of Shari’a financial institutions like Shari’a Bank, Shari’a insurance, Shari’a money market, etc ini order that such all institutions run in accordance with the demand of Islamic Shari’a. Supervision is either on the basis of Shari’a financial products or the management and the administration of Shari’a financial institutions, which matches with the Shari’a. DPS isn’t involved directly in the managerial practice of Shari’a financial institutions because it has been the responsibility, directly, under the directorate’s authority of a Shari’a financial institutions, but DPS has the right to give input toward the managers of the institutions. There are still more Shari’a financial institutions such as Shari’a bank, which hasn’t yet benefit maximally the rule and the function of DPS in its institution. More over, the improvement of professionalism for DPS’s members in performing the community mandate is not maximal yet. Requested on the future, DPS does become an institution, which is able to empower its rule and function for the development of Shari’a banking in Indonesia.